Fluid intake and blood pressure in children: the Salus per Aquam project. Issue 1 (30th January 2022) - Ardissino, Gianluigi; Perrone, Michela; Ghiglia, Silvia; Salice, Patrizia; Tel, Francesca; Dardi, Elena; Bollani, Tiziana; Mezzopane, Antonella; Capone, Valentina; Ardissino, Maddalena; Vergori, Antonio; Piantanida, Sandra; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Sodium intake is known to contribute to the development of hypertension, thus intake reduction is a cornerstone in the prevention and management of hypertension. The increase in renal sodium excretion might represent a further potential preventive and/or therapeutic opportunity. Objective: To explore the working hypothesis that an increased fluid intake can improve renal sodium handling towards a decrease in blood pressure. Methods: The SPA Project is a multicenter, observational, cross-sectional, cohort study investigating healthy children, aged 5–8 years as to sodium and fluid intake by means of urinary sodium and creatinine from multiple samples taken in different days in order to characterize them in lower/higher sodium and lower/higher fluid intake. Both SBP and DBP (by multiple office blood pressure measurements) were used as outcome measures. Results: Three hundred and thirty-nine healthy, nonoverweight children (51.6% boys) with a median age of 5.7 years old (IQR: 5.3–6.2) participated in the study but only 223 could be analyzed. Among children with higher sodium intake, those introducing more fluids, showed a significantly lower blood pressure (both systolic and diastolic) compared with those with lower fluid intake: systolic 86.0 ± 8.5 vs. 90.0 ± 8.1 mmHg; P = 0.014 and diastolic: 53.8 ± 4.9 vs. 58.6 ± 6.6 mmHg; P < 0.0001. Conclusion: An increased fluid intake is associated with a reduced blood pressure possibly by increasing renal sodium excretion. We speculate that this simple, highly acceptable, inexpensive, and harmless measure might have a role in preventing and/or minimizing the epidemics of hypertension and of its related morbidities both in children and in adults.